Insecta of Tungonan, Kananga, Leyte - Pastor, Trinidad M. (Leyte-Samar Studies, 1967)
In a joint venture with San Carlos University, the Divine Word University undertook its first scientific expedition to Tungonan, a barrio of Kananga, Leyte. The expedition had the following objectives: 1. To start an entomological collection for the University Biology Department. 2. To survey insect densities on mid-mountain elevations and in forest areas. 3. To observe the effects of volcanic environment on the ecology of insects.